Isolation and structures of eudesmanolides from Tanacetum cadmeum ssp cadmeum - Çaliskan, Z; Gören, N; Watson, WH (SPRINGER/PLENUM PUBLISHERS, 2004)
Eight sesquiterpene lactones, two coumarins, and two flavonoid derivatives were isolated from Tanacetum cadmeum (Boiss.) Heywood ssp. cadmeum. All compounds have been found previously in other plant species. The crystal structures of artesin and taurin are reported. Crystals of artesin (C15H22O3) belong to the monoclinic space group P2(1): a = 8.300(1), b = 6.304(1), c = 13.118(2) Angstrom, beta = 101.836(3)degrees, V = 671.8(2), Z = 2, R-1 = 0.0291. Crystals of taurin belong to the monoclinic space group P2(1): a = 5.722(1), b = 8.279(2), c = 14.503(3) Angstrom, beta = 90.025(1)degrees , V = 687.0(3), Z = 2, R-1 = 0.0493. An investigation of the space group indicated a monoclinic system rather than orthorhombic.
Keywords: sesquiterpenes eudesmanolides; isolation; crystal structure; ARGENTEUM SUBSP CANUM; SESQUITERPENE LACTONE; ARTEMISIA; COMPOSITAE; CHEMISTRY; Crystallography; Spectroscopy